2000
DOI: 10.1038/sj.bjp.0703723
|View full text |Cite
|
Sign up to set email alerts
|

Block of the lymphocyte K+ channel mKv1.3 by the phenylalkylamine verapamil: Kinetic aspects of block and disruption of accumulation of block by a single point mutation

Abstract: 1 Phenylalkylamines (PAA) usually known for their action on L-type Ca 2+ channels potently block the C-type inactivating lymphocyte Kv1.3 channel resulting in inhibition of activation of T lymphocytes. In order to design PAAs blocking Kv1.3 speci®cally over L-type Ca 2+ channels, we investigated the state-dependent manner of mKv1.3 block by the PAA verapamil. 2 Verapamil seems to have access to the open state (OB) and, once bound to the channel, the channel-verapamil complex is absorbed into a slowly recoverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 34 publications
5
27
0
Order By: Relevance
“…The observation that verapamil block was independent of the current-eliciting potential was unexpected but is consistent with results obtained for verapamil block of K ϩ channels (DeCoursey, 1995;Robe and Grissmer, 2000). One possibility is that verapamil binds outside of the transmembrane electric field.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The observation that verapamil block was independent of the current-eliciting potential was unexpected but is consistent with results obtained for verapamil block of K ϩ channels (DeCoursey, 1995;Robe and Grissmer, 2000). One possibility is that verapamil binds outside of the transmembrane electric field.…”
Section: Discussionsupporting
confidence: 76%
“…However, the lack of a substantial drug effect on the time course of T-channel currents suggests that the kinetics of inhibition are distinct from those observed for other channel targets. It is noteworthy that verapamil did not accelerate current decay as has been reported in L channels (Johnson et al, 1996;Dilmac et al, 2004) and K ϩ channels (DeCoursey, 1995;Catacuzzeno et al, 1999;Robe and Grissmer, 2000); in addition, the drug unbinding reaction could not be observed in the tail currents (data not shown) as in K ϩ channels (DeCoursey, 1995;Catacuzzeno et al, 1999;Robe and Grissmer, 2000). The dependence on holding potential was strongly suggestive of high-affinity drug binding to an inactivated state of the channel.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Indeed, clinical trials of Ca 2ϩ -active reagents have already been reported (50, 56 -58), e.g., verapamil, a HVA Ca 2ϩ channel blocker, has been used in vitro and in combined therapy approaches (48 -52). At higher doses, verapamil also blocks potassium channels (59), which may lead to some ambiguity in its mechanism of action. CAI is a promising anticancer agent acting on NVG channels, which is in Phase I and II clinical trials (56 -58).…”
Section: Discussionmentioning
confidence: 99%